Alternativas de mejora en el manejo postcosecha de tomate riñón cultivados en la provincia de Santa Elena - Coronel León, Jonathan (2010)
This research was part of the study of different post field level and its influence on the life and functional quality of it. The purpose is to recommend management operations tomato post currently affecting the life loss and tomato crops from the Santa Elena Peninsula. For the development of this is implemented the use of alternative materials in the process of packing the same way we stu influence of temperature on tomato quality and better packaging was determined as the temperature where the smallest losses were quantified.